Qualitative research in education : a user's guide - Lichtman, Marilyn (SAGE, 2010)
Qualitative Research in Education: A User's Guide, Second Edition brings together the essential elements of qualitative research, including traditions and influences in the field and practical, step-by-step coverage of each stage of the research process. Synthesizing the best thinking on conducting qualitative research in education, Marilyn Lichtman uses a conversational writing style that draws readers into the excitement of the research process. --from publisher description.